Amelioration of stress in broiler chickens by feeding amla - NAKAJOTHI, N; NANJAPPAN, K; SELVARAJ, P; JAYACHANDRAN, S; VISHA, P (The Indian Journal of Animal Sciences, 2011)
An experiment was carried out to test the efficacy of supplementing amla (Emblica officinalis) in broiler chickens diet from 1 to 6 weeks of age. Stress was induced by injecting adrenocorticotrophic hormone for 5 days from 22 d of age @ 3 IU / kg body weight. Amla fruits were dried and pulverized. The dietary treatments were T1 (standard diet with 0.0% amla), T2 (standard diet with 0.5% amla), T3 (standard diet with 1.0% amla), T4 (standard diet with 2.0% amla), T5 (standard diet with 250 mg/kg diet vitamin C). Blood samples were collected on d 21, 28 and 42 to measure the plasma antioxidants such as glutathione peroxidase (GSH-Px), reduced glutathione (GSH), superoxide dismutase (SOD), malonaldehyde (MDA) and plasma corticosterone and serum thyroxin. Results showed that MDA level was reduced significantly in amla and vitamin C fed groups compared to control. However, GSH-Px, SOD, GSH and thyroxin level did not vary significantly between treatment groups. The plasma corticosterone level was significantly reduced in amla and vitamin C supplemented groups groups compared to control. It can be concluded that supplementing broiler diet with amla powder at 0.5% or at higher level can act as antistress agent in broiler chicken production.Â